Mixed-mode I-II mesoscale fracture behavior of concrete determined by the realistic aggregate numerical model. (30th November 2019) - Jiangjiang, Yu; Guodong, Li; Zhengyi, Ren; Wei, Zhang; Jiangqi, Tang; Li, Zhang; Xiaolong, Si; Zhimeng, Zhao
Highlights: The meso-numerical model, corresponding to the realistic aggregate distribution, was established. The spatial distribution of the coarse aggregate determines the meso-mechanical properties of concrete and then affects the macro-mechanical behavior. To reduce the cracking risk of concrete, the volume fraction and gradation of aggregate should be kept within an appropriate range. Abstract: In this study, the aggregate information in concrete was extracted by Digital Image Processing (DIP) technology, and the two-dimension three-phase (coarse aggregate, mortar, and interface transition zone) meso-numerical model corresponding to the realistic aggregate distribution was established. Based on the model, considering the effects of coarse aggregate distribution, volume fraction and size on the fracture behavior, the fracture test and numerical simulation of four-point shear beams with notches under mixed-mode I-II stress were carried out. The results showed that the concrete meso -numerical model based on real aggregate can accurately reflect the meso-scale fracture process of concrete, and cracks always develop along the weak interface transition zone. It is the aggregate in the fracture trend zone that makes the fracture path tortuous, and the bending and shearing stress around the aggregate will change substantially. Moreover, the external force work of numerical model increases with the increase of aggregate volume fraction and maximum aggregate size, and the dissipated energy of coarse aggregate with small particle size increases with the rise in its proportion in gradation. Especially, the spatial distribution of the coarse aggregate determines the meso-mechanical properties of concrete and then affects the macro-mechanical behavior. To reduce the cracking risk of concrete, the volume fraction and gradation of aggregate should be kept within an appropriate range.